Respuestas
Respuesta dada por:
0
Hola....
x (x+3) = 270
![x^{2} + 3x=270 x^{2} + 3x=270](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+3x%3D270)
![x^{2} = \frac{270}{3} x^{2} = \frac{270}{3}](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%3D++%5Cfrac%7B270%7D%7B3%7D+)
![x^{2} =90 x^{2} =90](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%3D90)
![x^{} = \sqrt{90}
x^{} = \sqrt{90}](https://tex.z-dn.net/?f=+x%5E%7B%7D+%3D++%5Csqrt%7B90%7D+%0A)
![x^{}= 3 \sqrt{10} x^{}= 3 \sqrt{10}](https://tex.z-dn.net/?f=+x%5E%7B%7D%3D+3+%5Csqrt%7B10%7D+)
x (x+3) = 270
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años